The body in the casket ebook A faith fairchild mystery. - Page, Katherine Hall (Faith Fairchild, 2017)
The inimitable Faith Fairchild returns in a chilling New England whodunit, inspired by the best Agatha Christie mysteries and with hints of the timeless board game Clue. For most of her adult life, resourceful caterer Faith Fairchild has called the sleepy Massachusetts village of Aleford home. While the native New Yorker has come to know the region well, she isn't familiar with Havencrest, a privileged enclave, until the owner of Rowan House, a secluded sprawling Arts and Crafts mansion, calls her about catering a weekend house party. Producer/director of a string of hit musicals, Max Dane—a Broadway legend—is throwing a lavish party to celebrate his seventieth birthday. At the house as they discuss the event, Faith's client makes a startling confession. "I didn't hire you for your cooking skills, fine as they may be, but for your sleuthing ability. You see, one of the guests wants to kill me." Faith's only clue is an ominous birthday gift the man received the week before—an empty casket sent anonymously containing a twenty-year-old Playbill from Max's last, and only failed, production—Heaven or Hell. Consequently, Max has drawn his guest list for the party from the cast and crew. As the guests begin to arrive one by one, and an ice storm brews overhead, Faith must keep one eye on the menu and the other on her host to prevent his birthday bash from becoming his final curtain call. Full of delectable recipes, brooding atmosphere, and Faith's signature biting wit, The Body in the Casket is a delightful thriller that echoes the beloved mysteries of Agatha Christie and classic films such as Murder by Death and Deathtrap.